Revealing Stories of Artistic Identity Through Fabric Bricolage - Probine, Sarah; Jackson, Jayne; Enache, Mihaela; Ewing, Robyn; Crosbie, Jane; Stewart, Jean (Informa UK Limited, 2026)
This article presents and discusses the products of a creative workshop for artist/teachers which aimed to explore artistic identity through fabric bricolage, a medium unfamiliar to the participants. The account of the workshop and the artifacts created reveala the efficacy of a process that fostered reflection, honored complexity, included relational knowing, and affirmed the power of arts-based methods to reveal, connect, reframe, and transform. The article illustrates how individual acts of making, through the tactile, symbolic, and historically rich process of quilt-making, became a collective quilt of experience. The discussion points to the potential for further application in teacher education, professional development, and community arts contexts; any space where identity, creativity, and connection are valued. In a time when the arts continue to be marginalized in formal education and public discourse, creating spaces where creativity can be reawakened and meaning co-constructed is not just enriching, it is essential.
Keywords: 4702 Cultural Studies; 36 Creative Arts and Writing; 3901 Curriculum and Pedagogy; 3903 Education Systems; 39 Education; 47 Language, Communication and Culture; 4 Quality Education; 1302 Curriculum and Pedagogy